Primary health care tasks related to the care of chronically ill children - Pluta, Agnieszka; Marzec, Alicja; Faleńczyk, Kamila; Budnik-Szymoniuk, Maria; Kujawa, Wiesława; Basińska-Drozd, Halina (Journal of Education, Health and Sport, 2018)
An intensive increase in the occurrence of chronic diseases in the population of children and adolescents is observed. These diseases may disturb the child’s psycho-physical development process and the education process. Early diagnosis and coordinated therapy at the level of primary care may limit these disorders. The work of a nurse in the teaching and upbringing environment, which is a link between communication between the health care system and the school environment, is invaluable. Its full range of services allows early detection of disorders in the development and health of the child and development of an individual childcare plan with the parent and teachers taking into account the teaching process. The aim of the work was to present the tasks of the primary care system in the provision of care for chronically diseases children.